Pengambilan Data Inklinasi Dan Azimuth Dalam Proses Measurement While Drilling (MWD) Menggunakan Metode Mud-Pulse Telemetry Pada Sumur X Lapangan Y - Geusan Buana Fauzan; M.Mahlil Nasution; Citra Wahyuningrum (Jurnal Bhara Petro Energi, 2024)
The Measurement While Drilling (MWD) process is essential in the oil and gas industry to obtain real-time data during drilling operations. One of the MWD methods commonly used is mud- pulse telemetry, which transmits data through mud pulses generated by the drilling fluid. This study focuses on the data acquisition process on MWD using Mud-pulse telemetry at Well X, which is located in Field Y. The purpose of this research is to analyze the performance  of the MWD system, evaluate the quality of the data obtained through mud-pulse  telemetry. The results showed that from the results of well X data, Mud Pulse Telemetry with Continuous Wave System can transmit data continuously and in real time and can measure up to a depth of 1,268 meters. The advantage of Mud Pulse Telemetry is that mud pulses can transmit data with a signal  without  being disturbed by interference  from signals  inside  the earth,  so the  resulting noise tends to be a little lack ing in it. Despite the advantages of mud pulses, there are also disadvantages. One drawback  is when there is a loss of circulation. Lost Circulation is the loss of drilling mud into the formation. This study recommends  actions  to optimize  drilling  conditions and fluid properties  to improve  the accuracy and reliability of MWD data.